Pendampingan dan Edukasi Pembukaan Program Tahsin dan Tahfidzul Qur’an dalam Rangka Pemberantasan Buta Aksara al-Qur’an - Amirudin, Amirudin; Putra, Ary Antony; Supriady, Harif; Widodo, Widodo; Lestari, Keken; Hasna, Adis Rodiah (UIR Press, 2025)
This community service program aims to provide assistance and education in the implementation of tahsin and tahfidzul Qur'an programs in Merbau Village, Bunut District, Pelalawan Regency. This initiative is presented as a strategic step in an effort to eradicate Qur'an illiteracy which is still a challenge among the local community. Through this program, it is hoped that the community can better understand and practice the values contained in the Qur'an, thus not only improving their ability to read the Qur'an, but also strengthening their faith and devotion. This assistance is carried out by following a series of steps, including preparation, coordination with partner foundations, coordination with the village government, education about tahsin and tahfidzul Qur'an programs, assistance in signing the MoU between the two parties, and support in establishing an independent foundation. By involving various related parties, this service program is expected to help overcome the problem of Qur'an illiteracy in the community. The result of this program is the increasing number of community members who are able to read and memorize the Qur'an, so that overall it can reduce the number of Qur'an illiteracy in Merbau Village and its surroundings.